Does revenue‐motivated policing alter who receives traffic citations? Evidence from driver race and income in Indiana. (25th January 2023) - Mughan, Siân; Singla, Akheil
Abstract: Revenue‐motivated policing is a common explanation for law enforcement behavior. This means in times of fiscal stress police alter their behavior to increase the financial returns to their actions. But does variation in the institutional features of local governments lead to variation in law enforcement behavior? Using a plausibly exogenous measure of revenue need, this research explores how fiscal institutions that determine a local government's ability to retain ticketing revenue interact with revenue need to affect the number of tickets issued and the type of driver ticketed. There are four major findings. First, revenue‐motivated policing only occurs when local governments retain the revenues from ticketing. Second, in the context of revenue retention and high revenue need, wealthier drivers are more likely to receive tickets. Third, these effects are particularly pronounced among White drivers. Finally, revenue‐motives extend beyond law enforcement by altering judicial decision‐making. When general purpose governments do not retain ticketing revenues from law enforcement action, there is little evidence of revenue‐motivated policing. Municipal courts play a vital role in revenue‐motivated policing by determining the distribution of ticketing revenues. When a municipality has an increased need for additional revenue, judges pursue unpaid ticketing debts more aggressively. Judicial behavior is thus affected by the same fiscal pressures that lead police to engage in revenue‐motivated policing. Increased revenue need leads police to target drivers who are not typically the subject of enforcement actions: wealthier, white drivers. We find no such effect for Black drivers. Policies altering revenue retention are a promising way to reduce revenue‐motivated policing. But reducing revenue‐motivated policing might not improve outcomes for Black drivers.